(untitled) (Shanti Journal, 2024)
The shift from Digital Bangladesh to Smart Bangladesh signifies a noteworthy development in Bangladesh’s technology environment, mirroring goals for a thorough digital overhaul. This essay explores the difficulties that arose throughout this shift and suggests some viable alternatives to clear the path. The digital divide, cybersecurity risks, governance concerns, and infrastructure limitations are among the major obstacles that are identified by means of a thorough examination of regulatory frameworks, technology infrastructure, and socioeconomic aspects. Additionally, it investigates how these difficulties may affect Bangladesh’s vision for a Smart Bangladesh’s goals of achievement. In order to successfully address these difficulties, the study provides strategic suggestions based on empirical facts and insights from the current literature. These include building inclusive digital governance, bolstering cybersecurity precautions, encouraging innovation ecosystems, and improving digital infrastructure. Bangladesh may speed its road towards a genuinely smart and inclusive society and overcome obstacles to its digital transformation by putting these proposals into practice. Through practical observations and suggestions for overcoming obstacles in the transition from Digital Bangladesh to Smart Bangladesh, this study adds to the conversation on digital development.